Kegilaan dalam Novel Racun Puan Karrya Ni Nyoman Ayu Suciatrini: Tinjuauan Psikologi Sastra - Khairani, Nabila (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
This research delves into the theme of madness in the novel